Floriculture and Ornamental Plants - Datta, S. K.; Gupta, Youdh Chand (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The volume on oilseed crops is developed as a part of a series on "Handbook of Agrobiodiversity: Conservation and Use of Plant Genetic Resources". The handbook would function as a ready reference book for availability of PGR globally, along with specific source, wherefrom they can be procured, and used breeding programs, particularly to overcome various crop production constraints and to improve productivity and quality. The volume on floriculture and ornamental plants will be the source of basic information on origin and evolution and global dispersal of cultivated species of ornamentals. Presently, floriculture has established its credibility in improving income through increased productivity, generating employment and in enhancing exports. All research and developmental activities on ornamental crops are essentially multi-disciplinary in nature recognizing local issues as well as country issue. Floriculture is developing as an area of high technology based frontier interdisciplinary area on scientific excellence. Floriculture has progressed both scientifically and commercially due to concentrated efforts made on multidisciplinary research. It is developing as an area of high technology based frontier interdisciplinary area on scientific excellence. The volume will contain all information about different ornamentals. This shall be put together to develop a complete documentation of the results of the research and demonstrations conducted by different scientists. The volume will provide an illustrated horto-taxonomical account of important ornamental species and cultivars, germplasm status and their usages, propagation, nursery management, techno-economics, conventional breeding, induced mutagenesis, new varieties, cytogenetics, tissue culture, characterization of varieties, dehydration of flowers etc. This volume will give a coherent and concise account on recent developments. It will deal with all the important and relevant aspects of floriculture. The publication of this volume is planned to reveal multifarious activities done on different aspects of floriculture so that innovations made so far can be used judiciously for this sector. This book shall provide authoritative review account of many aspects of current interest and progress in the field of floriculture. The topics included in the book are interdisciplinary and cater not only classical floriculture but also relevant modern aspects. The book will provide valuable data on different aspects and will be widely accepted by by professional scientists, researchers, teachers, students, floriculturists, technocrats and planners. The volume will be an invaluable asset to floriculture scientists.
Marigold -- Bougainvillea -- Carnation -- Chrysanthemum -- Gladiolus -- Lilium -- Alstroemeria -- Rose -- Tulip -- Annuals -- Traditional bulbous plants -- Pot plants -- Orchids -- Landscaping -- Gerbera -- Jasmine -- Tuberose -- Hibiscus -- Modern techniques for plant breeding in ornamentals -- Dischidia, Medinilla and Nepenthes -- Value Addition: Dehydration of Flowers and Foliage and Floral Craft.
Keywords: Plant biotechnology; Plants-Evolution.; Biodiversity; Plants-Development.; Agriculture; Plant Biotechnology; Plant Evolution; Biodiversity; Plant Development; Agriculture